A 9-gene biomarker panel identifies bacterial coinfections in culture-negative COVID-19 cases. Issue 8 (16th August 2022) - Banerjee, Ushashi; Rao, Pragati; Reddy, Megha; Hussain, Meeran; Chunchanur, Sneha; Ambica, R.; Singh, Amit; Chandra, Nagasuma
Abstract : Confirmatory diagnosis of bacterial coinfections with COVID-19 is challenging due to limited specificity of the gold-standard culture sensitivity test. This study presents a host gene signature to diagnose bacterial coinfection with high confidence. Abstract : Confirmatory diagnosis of bacterial coinfections with COVID-19 is challenging due to the limited specificity of the widely used gold-standard culture sensitivity test despite clinical presentations. A misdiagnosis can either lead to increased health complications or overuse of antibiotics in COVID-19 patients. With a multi-step systems biology pipeline, we have identified a 9-gene biomarker panel from host blood that can identify bacterial coinfection in COVID-19 patients, even in culture-negative cases. We have also formulated a qPCR-based score that diagnoses bacterial coinfection with COVID-19 with the accuracy, specificity, and sensitivity of 0.93, 0.96, and 0.89, respectively. This gene signature and score can assist in the clinical decision-making process of necessary and timely prescription of antibiotics in suspected bacterial coinfection cases with COVID-19 and thereby help to reduce the associated morbidity and mortality.